Differences in Nuclear DNA Organization Between Lymphocytes, Hodgkin and Reed–Sternberg Cells Revealed by Structured Illumination Microscopy. Issue 8 (August 2014) - Righolt, Christiaan H.; Guffei, Amanda; Knecht, Hans; Young, Ian T.; Stallinga, Sjoerd; van Vliet, Lucas J.; Mai, Sabine
ABSTRACT Advances in light microscopy have enabled the visualization of DNA in the interphase nucleus with more detail than is visible with conventional light microscopy. The nuclear architecture is assumed to be different in cancer cells compared to normal cells. In this paper we have studied, for the first time, the organization of nuclear DNA and that of DNA‐free space in control lymphocytes, Hodgkin cells and Reed–Sternberg cells using 3D structured illumination microscopy (SIM). We have observed detail in these SIM images that was not observed in conventional widefield images. We have measured the size distribution of the DNA structure using granulometry and noted a significant, progressive increase in the amount of sub‐micron structures from control lymphocytes to Hodgkin cells to Reed–Sternberg cells. The DNA‐free space changes as well; "holes" in the DNA distribution start to appear in the malignant cells. We have studied whether these "holes" are nucleoli by staining for upstream binding factor (UBF), a protein associated with the nucleolus. We have found that the relative UBF content progressively and significantly decreases—or is absent—in the DNA‐free space when measured as either the Pearson correlation coefficient with the DNA‐free space or as the number of "holes" that contain UBF. Similar differences exist within the population of Reed–Sternberg cells between binucleated and multinucleated cells with four or more subnuclei. To our knowledge, this is the first study that investigates the changes of the nuclear DNA structure in any disease with superresolution light microscopy. J. Cell. Biochem. 115: 1441–1448, 2014. © 2014 The Authors. Journal of Cellular Biochemistry published by Wiley Periodicals, Inc. This is an open access article under the terms of the Creative Commons Attribution‐NonCommercial‐NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non‐commercial and no modifications or adaptations are made.